1995
DOI: 10.3109/00365529509101633
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Status in End-Stage Liver Disease and the Effect of Liver Transplantation

Abstract: Early and accelerated bone loss occurred after liver transplantation. This bone reduction seems to be mainly the result of increased bone resorption, possibly related to corticosteroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 18 publications
6
24
1
Order By: Relevance
“…Immunosuppressive drugs certainly play a major role in this setting [10,11]. Although the alterations seen in bone metabolism after liver transplantation have been mainly attributed to the use of glucocorticoids [4][5][6]19], most authors failed to demonstrate this relationship. This is probably due to the fact that the majority of studies concentrated on an early phase after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive drugs certainly play a major role in this setting [10,11]. Although the alterations seen in bone metabolism after liver transplantation have been mainly attributed to the use of glucocorticoids [4][5][6]19], most authors failed to demonstrate this relationship. This is probably due to the fact that the majority of studies concentrated on an early phase after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Strongest was the association between hyponatremia and liver insufficiency, which is also known to negatively impact bone metabolism, seemingly irreversible despite liver transplantation for end-stage liver disease [27][28][29][30]. Several markers of protein synthesis, clotting factor production, and cholestasis were significantly altered in hyponatremic patients, i.e., elevated levels of ALAT, bilirubin count, cobalamin, GGT, and APTT, while albumin levels were significantly lower.…”
Section: Hyponatremia As a Marker Of Secondary Osteoporosismentioning
confidence: 96%
“…8 The mechanisms underlying this early increase have not been established but may be related to vitamin D deficiency, intestinal calcium malabsorption,or reduced renal tubular reabsorption of calcium. An increase in plasma parathyroid hormone levels has been more consistently noted after longer-term followup 15,20,22,23,27,33 and may be related to cyclosporin-induced renal dysfunction.…”
Section: Secondary Hyperparathyroidismmentioning
confidence: 99%
“…12,19 Low bone mineral density in patients awaiting liver transplantation has been reported in a number of studies 17,33,51,55,57 although this finding has not been universal. 20 In a study of 243 consecutive patients with chronic liver disease undergoing assessment for liver transplantation, Ninkovic et al reported that 36.6% had osteoporosis according to WHO criteria 58 (a T score below -2.5) and bone mineral density was normal (T score above -1) in only 15.2%. 57 Importantly, men and women were equally affected and with the exception of increasing age and lower body weight in women, no independent risk factors were identified, emphasising the importance of bone mineral density measurements in these patients.…”
Section: Pre-existing Bone Diseasementioning
confidence: 99%
See 1 more Smart Citation